Adaptive Leadership Di Organisasi Pemuda NU - Khoirun Nisa’; Wahyu Eko Pujianto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Adaptive leadership is about helping people to change and adapt to new situations. Leaders are required to be able to analyze, see and formulate all forms and types of organizational problems. On the other hand, if the leader only has a bad character and does not have a good influence on his members, then it is certain that the organization will not develop well and according to expectations. The aim of this research is to analyze why the role of adaptive leadership is so important in the IPNU and IPPNU organizations, and how the adaptive leadership process plays out in developing the organization. This research method uses qualitative methods. The research will conduct interviews at the IPNU and IPPNU organizations in Sedati District and will conduct interviews with 18 branches. The data analysis technique in this research uses interactive model data analysis techniques. The research results found that not all IPNU and IPPNU leaders in Sedati District implemented adaptive leadership well.